Bioactive substances with anti-neoplastic efficacy from marine invertebrates: Porifera and Coelenterata - Sima, Peter; Vetvicka, Vaclav (World journal of clinical oncology, 2011)
An ever increasing demand for new lead compounds in the pharmaceutical industry has led scientists to search for natural bioactive products. Based on this extensive research, marine invertebrates now represent a rich source of novel substances with significant anti-neoplastic activities. As the current approach of synthesizing new and chemically modifying old drugs seems to have slowed down, and the identification of new anticancer drugs is not too promising, a new approach is clearly needed. The objective of this review is to present up-to-date data on these newer compounds. Based on the data summarized in this short review, it is clear that marine invertebrates represent an extremely important source of compounds with potential anti-cancer effects. Considering that we tested only a tiny number of Porifera and Coelenterata, the best is yet to come.
Keywords: Invertebrates; Coelenterata; Porifera; Cancer